High-resolution mechanical imaging of the human brain by three-dimensional multifrequency magnetic resonance elastography at 7T - Braun, Juergen; Luetzkendorf, Ralf; Stadler, Joerg; Papazoglou, Sebastian; Hirsch, Sebastian; Bernarding, Johannes; Sack, Ingolf; Guo, Jing (NeuroImage, 2014)
Magnetic resonance elastography (MRE) is capable of measuring the viscoelastic properties of brain tissue in vivo. However, MRE is still limited in providing high-resolution maps of mechanical constants. We therefore introduce 3D multifrequency MRE (3DMMRE) at 7T magnetic field strength combined with enhanced multifrequency dual elasto-visco (MDEV) inversion in order to achieve high-resolution elastographic maps of in vivo brain tissue with 1mm3 resolution. As demonstrated by phantom data, the new MDEV-inversion method provides two high resolution parameter maps of the magnitude (|G*|) and the phase angle (φ) of the complex shear modulus. MDEV inversion applied to cerebral 7T-3DMMRE data of five healthy volunteers revealed structures of brain tissue in greater anatomical details than previous work. The viscoelastic properties of cortical gray matter (GM) and white matter (WM) could be differentiated by significantly lower values of |G*| and φ in GM (21% [P<0.01]; 8%, [P<0.01], respectively) suggesting that GM is significantly softer and less viscous than WM.In conclusion, 3DMMRE at ultrahigh magnetic fields and MDEV inversion open a new window into characterizing the mechanical structure of in vivo brain tissue and may aid the detection of various neurological disorders based on their effects to mechanical tissue properties. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Brain tissue; Elastography; High resolution; Multifrequency MRE; Ultrahigh magnetic field MRI; Viscoelastic parameters